Prevalence and factors associated with depression among the mothers of school-going children in Dhaka city, Bangladesh: A multi stage sampling-based study. Issue 7 (July 2021) - Sultana, Sharmin; Zaman, Sanjana; Chowdhury, ABM Alauddin; Hasan, Istiaque; Haque, Md. Imdadul; Hossain, Md. Kamrul; Ahmed, Kazi Rumana; Chakraborty, Promit Ananyo; Hossain Hawlader, Mohammad Delwer
Abstract: Background: Motherhood is associated with extra stress, and mothers of young children are particularly prone to developing depression and mental health problems. Methodology: This analytical cross-sectional study was conducted in Dhaka city, Bangladesh, from June to December 2019. Mothers of school-going children were recruited through a multistage sampling technique. Dhaka city was divided into two divisions and then further subdivided into public and private sectors. Six schools were selected from each sector by using a simple random sampling technique. A list of class five to eight students were collected from each school by systematic random sampling. Data were collected through face-to-face interviews using semi-structured questionnaires. The rate of depressive symptoms was measured by the validated Zung Self-Rating Depression Scale (SDS). Result: A total of 324 women participated in this study; the majority of the women (85.5%) were Muslim, 67.0% were housewives, and 53.1% had a girl child. Among the women, 15.4% had mild, 22.2% had moderate, and 20.1% had severe depression. Most of the child's behavioral and lifestyle factors were associated with the mother's depression. Adjusted analyses indicate that if a child is often unhappy, depressed, or tearful [(OR (95%CI = 22.27 (8.39–59.11)], gets nervous in new situations or easily loses confidence [(OR (95%CI) = 5.45 (2.96–10.00)], often lies or cheats [(OR (95%CI) = 8.93 (3.76–21.22)], gets afraid easily [(OR (95%CI) = 7.09 (3.79–13.24)], watches television for 3 h or more [(OR (95%CI) = 23.77 (6.46–87.48)] browses the internet for 3 h or more [(OR (95%CI = 7.37 (2.76–19.67)] were associated with mother's depression. Conclusion: The study concludes that depression among the mothers of school-going children in Dhaka city of Bangladesh is high. Several lifestyles and behavioral factors of school-going children are significantly associated with the mothers' depression. Abstract : Maternal depression, mothers, school-going children, Bangladesh